2019
DOI: 10.1002/jccs.201800325
|View full text |Cite
|
Sign up to set email alerts
|

Application of Cu(Hdmg)2 as a simple and cost‐effective catalyst for the convenient one‐pot reductive acetylation of aromatic nitro compounds

Abstract: In this article, we have developed a novel and simple one‐pot reductive acetylation of aromatic nitro compounds with sodium borohydride (NaBH4) in ethyl acetate (EtOAc) under reflux conditions in the presence of the bis(dimethylglyoximato)copper(II) complex [Cu(Hdmg)2] as an efficient and cost‐effective copper‐containing catalyst. Notably, using the above‐mentioned one‐pot reaction, the corresponding acetamide derivatives were obtained in high to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…The similar state of the art materials and others such as nanoparticles, composites and doped materials were compared with 1 for the sake of the progress of the reported procedure (Table 6). [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] By careful reading of the table, one can easily identify the reduction of nitro to amine utilized drastic conditions such as synthesis of the catalyst, use of noble metals or expansive metals, harsh H-source such as explosive H 2 or NaBH 4 , hydrazine hydrate, silanes, formats etc. and time of the reaction for the catalysts/amine formation.…”
Section: Catalytic Activity Ofmentioning
confidence: 99%
See 3 more Smart Citations
“…The similar state of the art materials and others such as nanoparticles, composites and doped materials were compared with 1 for the sake of the progress of the reported procedure (Table 6). [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] By careful reading of the table, one can easily identify the reduction of nitro to amine utilized drastic conditions such as synthesis of the catalyst, use of noble metals or expansive metals, harsh H-source such as explosive H 2 or NaBH 4 , hydrazine hydrate, silanes, formats etc. and time of the reaction for the catalysts/amine formation.…”
Section: Catalytic Activity Ofmentioning
confidence: 99%
“…However, in the present work we focus on synthetic strategy and selectivity towards CR of 1 with other reported adsorbents. Beheshti et al [36] and Mohammad et al [59] have reported synthesis of the Cd-based coordination polymers and Cd-MOFs respectively for dye adsorption, but it involves tedious synthesis procedure. Thus, 1 has an advantage of facile synthesis conditions and selective towards CR.…”
Section: Adsorption Studymentioning
confidence: 99%
See 2 more Smart Citations
“…In continuation of our research programs on various type of organic reactions [67][68][69][70][71], especially on the simple methodologies for the preparation of N-arylacetamides [72][73][74][75], we wish to report two different facile and efficient approaches for the synthesis of divers N-arylacetamides via N-acetylation of arylamines and straightforward one-pot reductive acetylation of nitroarenes promoted by recyclable CuFe 2 O 4 MNPs in water at reflux (Scheme 1).…”
Section: Dementioning
confidence: 99%